ANALYSIS OF BETTER BETTER JUICE AS AN INGREDIENT FOR MANUFACTURING AND SELLING CUPCAKES THROUGH FILTERING FROM THE PRODUCTS OF PARE FRUIT: ANALISA PENGAMBILAN SARI BUAH PARE SEBAGAI BAHAN PEMBUATAN DAN PENJUALAN CUPCAKE MELALUI PENYARINGAN DARI HASIL BUAH PARE - Feddya Ezrani, Delvi (LPPM UPMI, 2024)
Bitter gourd is a plant that grows a year and has a vine nature, with a small and long stem. Pare fruit can grow at an altitude of 0-250 m above sea level. can grow in various types of soil and thrives in sandy soil rich in loose organic matter with a pH of 5-6. Bitter gourds also don't need a lot of sun with low humidity Bitter gourds are famous for their bitter fruit. The plant, which has the Latin name momodica chrantia, has an elongated oval shape, is green, yellow to orange in color and tastes bitter. the seeds are hard and yellowish brown in color. this shows that bitter melon plants have spread throughout the area. It's just that, there is still much that is not known that bitter melon can actually be used to cure several diseases and improve human health. following the nutritional content of bitter gourd and bitter gourd leaves per 100 grams of ingredients Bitter gourd fruit has been widely used by humans as a medicine for African people to use bitter melon as an anti-diabetic, antipyretic, anti-goud, and so on. Several studies have explained that bitter melon has potential as an antioxidant, antitumor, neuroprotective, anti-inflammatory and antimicrobial. Bitter gourd extract contains complex compounds including insulin mimetics, vitamins, minerals and antioxidants. Insulin mimetics include quarantine, polypeptide – pvinin, vitamins found in bitter gourd include vitamins C, E, B1, B2, B3, and B9 (folate). Bitter gourd fruit also contains minerals, namely potassium, calcium, zinc, magnesium, phosphorus and iron as well as anti-oxidants in bitter melon fruit, namely phenols, flafonoids, insoflafones, terpenes, anthraquinones, and glucosinolates. from this matter the purpose of writing this article is to find out and analyze how to extract bitter melon juice which contains many nutritious substances for the health of the human body and how to make innovative cupcakes from bitter melon juice and from the results of this research we can also create new innovations which is made from bitter gourd which basically a lot of people who do not like the bitter gourd. and which in the end can introduce to the wider community that bauh pare can be used as processed snacks and dishes. this can teach that the younger generation can be more innovative with what is around them to further develop new innovations. From this, people who don't like bitter melon like bitter melon because there are various products made from bitter melon.